Precision livestock farming: a qualitative exploration of swine industry stakeholders - Akinyemi, Babatope E.; Vigors, Belinda; Turner, Simon P.; Akaichi, Faical; Benjamin, Madonna; Johnson, Anna K.; Pairis-Garcia, Monique D.; Rozeboom, Dale W.; Steibel, Juan P.; Thompson, David P.; Zangaro, Cassey; Siegford, Janice M. (Frontiers in Animal Science, 2023)
Precision livestock farming (PLF) technology development has proliferated recently, but on-farm adoption has lagged. Understanding PLF stakeholders’ views, practical applications, limitations, and concerns are necessary to understand the factors influencing the adoption of PLF technology. Using semi-structured online interviews, 12 influential stakeholders' PLF views and lived experiences were investigated. A phenomenological paradigm was used to generate qualitative data that was analyzed using template analysis. We identified two unique groups of stakeholders, namely the PLF enthusiast and PLF cautious groups. The majority of the participants were well aware and had firsthand experience with the PLF technologies that are currently being used in the swine industry. We found that PLF technology was perceived to improve specificity in decision-making, better care for pigs, improve animal health and welfare, increase labor efficiency, and improve resource-use efficiency. Poor internet connectivity and the inability to use PLF data for decision-making due to needing to first complete daily on-farm tasks were considered key obstacles to its implementation. To integrate PLF technology into the existing barn environment, it is necessary to modify farm buildings and infrastructure and management protocols. Stakeholders' main concerns with PLF technology included data privacy issues and the influence of PLF technology on human-animal relationships and farmers’ duty of care to the animals. In conclusion, stakeholders perceived camera systems for monitoring pig health and welfare and ensuring individual pig identification as a high priority in PLF development going forward.